OPTIMALIZING YOU TUBE VIDEOS TO IMPROVE STUDENTSâ TRANSLATION SKILL - -, Humaira (JURNAL SMART, 2018)
This study attempts to formulate the issues of YouTube in teaching translation courses of improving studentsâ skill. This research used classroom action research. The study was conducted at the VIII semester students in English education program FKIP-UM Mataram with total respondents were 25 students. The results showed a significant improvement related to the ability of studentsâ translation. It can be seen from the increase of the average value obtained by students at each stage. In try out, their average score is 5.6, then in cycle 1 increased to 6.75 and in cycle 2, the average student score increased to 7.3.